Imprinting and driving electronic orbital magnetism using magnons - Li-chuan Zhang (Nature Portfolio, 2020)
The chiral spin texture hosted by Kagome lattices is emerging as a prominent playground for investigating exotic phenomena related to topological quantum phases. Here the authors utilize a tight-binding approach to unveil the existence of spontaneous interactions capable of bridging the gap between magnonics and spin-orbitronics.